Uterus-preserving laparoscopic lateral suspension with mesh for pelvic organ prolapse: a patient-centred outcome report and video of a continuous series of 245 patients. Issue 3 (March 2016) - Veit-Rubin, Nikolaus; Dubuisson, Jean-Bernard; Lange, Sören; Eperon, Isabelle; Dubuisson, Jean
Abstract Introduction and hypothesis Changes in the psychological value of reproductive organs have led to a growing interest in uterine-preserving surgery for pelvic organ prolapse (POP). Sacral hysteropexy is considered as gold standard, although dissection of the promontory may be challenging. We show a video and present a report on a series of patients operated by laparoscopic lateral suspension with mesh as an alternative. Methods Clinical evaluation was performed using the simplified Pelvic Organ Prolapse Quantification System (POP-Q). Primary outcomes were subjective and objective cure; secondary outcomes were rates for reoperation and complications. We assessed patient's satisfaction in a telephone interview using a visual analogue scale and the Patient Global Impression of Improvement Scale (PGI-I) scale. Results Two hundred and fifty-four patients were treated between 2004 and 2011 with a median follow-up of 7.5 years. At 1 year 82.7 % of patients were asymptomatic, and anatomic success rates were 88.2 % for the anterior, 86.1 % for the apical and 80.8 % for the posterior compartment; 1.2 % had mesh exposure, and the reoperation rate was 7.4 %. More than 80 % of patients were highly satisfied with the outcome. Conclusions Uterine-preserving laparoscopic lateral suspension with mesh is a safe technique with promising results and low complication rates. It may be an alternative to sacral hysteropexy for high-morbidity patients.